PENERAPAN INSTRUMEN ASESMEN PERKEMBANGAN FISIK MOTORIK USIA 5-6 TAHUN DI PAUD GUDISEJU - Artha Mahindra Diputra; Rachel Sehulina, Sherly Mardini, Sherina Ayu Viana, Delta Fariza, Elsa Meriska (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
Understanding of the stages of growth and development can be done through an assessment process. Assessment namely a process of gathering information in order to make decisions. Collectio information in the form of data obtained through the process of observation with various tools assessments such as rating scales, checklists, rubrics. If the scope is early childhood development, then the decision taken is the provision of services or treatment in accordance withneeds and stages of development